It’s Happy Hour Somewhere: Videoconferencing Guidelines for Traversing Time and Space - Palalas, Agnieszka; Heiser, Rebecca E.; Gollert, Ashley (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
Time seems to be moving at lightning speed with busyness unsustainably being “celebrated” and not allowing for sufficiently deep interaction with learning content, others, and the experience of which we are part, including our interactions in videoconferencing sessions. One benefit of videoconferencing is that it can address time and distance boundaries. With this advantage also comes a challenge - the pressures of time and time not being used purposefully often negatively impact the online learning experience and the digital wellness of its participants. Considering that, the reported study inquired: what are the videoconferencing guidelines in relation to temporal space to support digital wellness in online learning in higher education? Drawing on a systematic review of the relevant literature of the last decade, temporal guidelines have been distilled to promote the design of videoconferencing-based learning that is conducive to successful learning while maintaining digital well-being. The article organizes the literature review findings according to the categories identified through the secondary data analysis of its three preceding studies. Based upon 42 articles that met the inclusion and exclusion criteria in the first phase of the research design, we negotiated and determined thirteen temporal guideline themes described as time management, essentialism, purposefulness, agility, social presence, attention, inclusion, cooperation, respect, technology preparedness, creativity, evaluation, and safety. Further research is recommended to explore the various aspects of design in more depth and tackle the less frequently addressed themes of creativity, evaluation, and safety, focusing on pedagogy and human-centred approaches.